Antisense RNAs during early vertebrate development are divided in groups with distinct features - Pillay, Sanjana; Takahashi, Hazuki; Carninci, Piero; Kanhere, Aditi (Genome Research, 2021)
Long noncoding RNAs or lncRNAs are a class of non-protein-coding RNAs that are >200 nt in length. Almost 50% of lncRNAs during zebrafish development are transcribed in an antisense direction to a protein-coding gene. However, the role of these natural antisense transcripts (NATs) during development remains enigmatic. To understand NATs in early vertebrate development, we took a computational biology approach and analyzed existing as well as novel data sets. Our analysis indicates that zebrafish NATs can be divided into two major classes based on their coexpression patterns with respect to the overlapping protein-coding genes. Group 1 NATs have characteristics similar to maternally deposited RNAs in that their levels decrease as development progresses. Group 1 NAT levels are negatively correlated with that of overlapping sense-strand protein-coding genes. Conversely, Group 2 NATs are coexpressed with overlapping protein-coding genes. In contrast to Group 1, which is enriched in genes involved in developmental pathways, Group 2 protein-coding genes are enriched in housekeeping functions. Group 1 NATs also show larger overlap and higher complementarity with the sense-strand mRNAs compared to other NATs. In addition, our transcriptomics data, quantifying RNA levels from cytoplasmic and nuclear compartments, indicates that Group 1 NATs are more abundant in the cytosol. Based on their expression pattern, cytosolic nature, and their higher complementarity to the overlapping developmental mRNAs, we speculate that Group 1 NATs function post-transcriptionally to silence spurious expression of developmental genes.